Creating a Database of Uzbek Dictionaries Related to the Text of "Boburnoma" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Automated information technologies and computers are gaining importance in our society today. This is causing the emergence of new directions. Corpus linguistics is considered an important branch of computer linguistics, and all research related to the science is inextricably linked with software and lexicography. National lexical wealth and possibilities of natural language are shown in dictionaries. Therefore, dictionaries are characterized by being in a machine-readable format, having a search engine, indexing, categorizing, clustering, and the ease and breadth of the user's ability to use it. The software provides a linguistic resource base with such perfect dictionaries. This article discusses the importance of dictionaries in these languages in creating parallel corpora, in particular, the Uzbek, Turkish and Kazakh parallel corpora of "Boburnoma" .